PEMBERDAYAAN MARKETING COMMUNICATION PADA PERUSAHAAN GEMILANG LIMA JAYA - Dewi, Liliana; Saputro, Tirza Natalia (STIE Mahardhika, 2019)
Gemilang Lima Jaya (GLJ) has done such a word of mouth promotion, personal selling, sales promotion, and advertising. But in fact, GLJ generates sales is low due to lack of brand awareness on a sandal with a brand of NIMS. The purpose of this study was to evaluate communication marketing that can support GLJ’s brand awareness. This type of research is a qualitative method with semi structured interviews with GLJ’s consumers, CEO of GLJ, lecturers who supervise the project and experts, and documentation in collecting data. The results showed that (1) the overall that marketing communication applied in support of brand awareness GLJ is still not effective (2) factor marketing communication that supports brand awareness is advertising. (2) Advertising and personal selling GLJ yet effective, the need for evaluation in improvingInstagram such as posting the supporting images and increase the intensity of advertising. Personal selling by increasing design stand, do partnership, and doexhibition surveys. (3) Word of mouth and sales promotion has been running quite effectively. Still, Word of mouth needs evaluation by expanding markets outside the community. Sales Promotion is in compliance with the target market GLJ, yet still needs to be improved by offeringpromotional goods such as stamp and voucher.